Short-Term Memory Loss Over Time Without Retroactive Stimulus Interference - Cowan, Nelson (2008)
A key question in cognitive psychology is whether information in short-term memory is lost as a function of time. Lewandowsky, Duncan, and Brown (2004) argued against that memory loss because forgetting in serial recall occurred to the same extent across serial positions regardless of the rate of recall. However, we believe Lewandowsky et al. only prevented one of two types of rehearsal; they did not prevent non-articulatory rehearsal via attention. To prevent articulatory and non-articulatory rehearsal without introducing interference, we presented unevenly-timed stimuli for serial recall and, on some trials, required that the timing of stimuli be reproduced in the response. In those trials only, evidence of memory loss over time emerged. Further research is needed to identify whether this memory loss is decay or lost distinctiveness.